PENGARUH WORKING CAPITAL TURNOVER, LONG TERM DEBT-TO-EQUITY RATIO, DAN RETURN ON EQUITY TERHADAP RETURN SAHAM (Studi Empiris pada Perusahaan-Perusahaan LQ45 Nonkeuangan Tahun 2010 - 2012) - Riswandha Adi Wibowo; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
This research was performed to examine the effect of working capital turnover, long term debt-to-equity ratio and return on equity on the stock return by nonfinancial companies listed in LQ45 index during 2010 – 2012. Independent variables in this study are working capital turnover, long term debt-to-equity ratio, and return on equity. Working capital turnover was measured by dividing companies’ net income with working capital. Long term debt-to equity ratio was measured by dividing companies’ long term liabilities with stockholders’ equity. Return on equity was measured by dividing companies’ profit after tax with stockholders’ equity. While the dependent variable in this study is stock return.The results of multple regression analysis showed that the usage of working capital turnover, long term debt-to-equity ratio and return on equity altogether had no significant impact on stock return. The partial t tests were resulted in negative nonsignificant effect of working capital turnover on stock effect, positive nonsignificant effect of return on equity on stock return, and nonsignificant negative effect of long term debt-to-equity ratio on stock return.